Method to Evaluate Consumption of Tourist Services in Regional Markets - TRETYAKOVA, Oksana V.; NIKITINA, Natalya I.; SPASSKAYA, Natalia V. (Journal of Environmental Management and Tourism; Vol 8 No 4 (2017): JEMT Volume VIII Issue 4(20) Summer 2017, 2017)
The paper aims at improvements of the toolkit designed for evaluation of the demand in tourism. The research focus includes a number of challenges that hamper the recreation and tourism development, solutions to which require a use of opportunities within the strategic approach to management. In the critical review, we have updated the specifics of the consumer demand and tourist product marketing. The authors summarized factors of regional tourism development, gave their grouping and description. They proposed the methodological approach to the estimation of a promising capacity in the regional tourism market. Piloting the approach as a model, they gave reasons for the conclusion that an increase in the purchasing demand for tourist services is one of the key factors of the external environment able to ensure a further growth in the tourism turnover. The authors have proved the hypothesis suggesting that the residents’ demand for national and international tours has its particular flexibility leading to an increase in national tourism at the expense of reduced international tourist flows and vice versa. A further direction of research might deal with spatial interregional links to achieve the potential of the tourism market.